If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(5x + -7) + -8x = -5 Reorder the terms: 4(-7 + 5x) + -8x = -5 (-7 * 4 + 5x * 4) + -8x = -5 (-28 + 20x) + -8x = -5 Combine like terms: 20x + -8x = 12x -28 + 12x = -5 Solving -28 + 12x = -5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '28' to each side of the equation. -28 + 28 + 12x = -5 + 28 Combine like terms: -28 + 28 = 0 0 + 12x = -5 + 28 12x = -5 + 28 Combine like terms: -5 + 28 = 23 12x = 23 Divide each side by '12'. x = 1.916666667 Simplifying x = 1.916666667
| 4xy+6xy= | | 6x+24=12x+14 | | 6x-(4x+7)= | | 5a+4(2a+4)= | | 3y-9y=102 | | 344x-78=78 | | 3x^2+3=6x | | 1. 3+8x+7=34 | | 2345x=567 | | 2345x-567=567 | | (x+3)2=(x+5)3 | | 4t^4+8-(3t^4+5)= | | x+5=x+(9-x) | | 2x^2-12x=14 | | 4(x+8)=6x+8 | | 13+x*12-18=271 | | -44=-8(1+4p)-4p | | 3(10x-2)=-4(-7x+11) | | -(41p-82q+80)= | | -42=2(7n+7) | | 2(5t-3)=3(2t+6) | | 5(2x-z)=7h | | x^3+2x^2-8x-16=0 | | 5(x-5)=x(14-4) | | 5(2x-4)=2(3x+2) | | -7(p+7)=-21 | | 38+x=2(11+x) | | 4(3x-5)=2(x-5) | | 6(m+3)=2(m-1) | | -1-x^2=0 | | 56=-8(1+n) | | 0=4+2x-2x |